Factors affecting Jordanian electronic banking services - Hassan Rawwash (Management Science Letters, 2020)
This study aimed to identify the factors influencing on electronic banking services provided by Jordanian banks. Perceived usefulness, ease of use, trust, privacy and security and convenience are the factors investigated in this study. A sample of 300 clients working at King Abdullah University Hospital staff who were active bank accounts in different local banks in Jordan was selected, randomly. To collect the primary data, the study used a questionnaire design based on a 5-point scale. Results of the study found that perceived usefulness, ease of use, trust and privacy directly and positively influenced on e-banking usage. Convenience was found to have no effect on e-banking services. The study recommends that an understanding the factors affecting e-banking is very essential for the practitioners who seek new ways of banking services in the current competitive environment.